Analisis Performansi Rantai Pasok Bawang Goreng Pada Industri Rumahan Azka Kabupaten Probolinggo - Amanda, Boyke Putra; Amir, Nur Ocvanny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Shallots are the largest agricultural production in Probolinggo Regency. Azka Home Industry processes red onions into fried onions to develop its business. However, there are several problems such as unstable prices and unstable supply of shallots. The objectives of this research are 1) to determine the product flow, money flow, and information flow in the fried onion supply chain flow at the Azka Home Industry. 2) to analyze the performance of the fried onion supply chain at the Azka Home Industry. Sampling used the "snowball sampling" method. Performance level analysis uses the "delivery performance" method with SOCR (Scheduled Order to Customer Request) calculations. The results of this research show 1) the product flow in the Azka Home Industry fried onion supply chain flows from upstream to downstream or from farmers to consumers, the flow of money is inversely proportional to the product flow, the money flow in the Azka Home Industry fried onion supply chain starts from consumers to farmers, the flow of information in the fried onion supply chain runs in two directions. 2) partner performance in the fried bang supply chain has very good criteria based on SOCR (Scheduled Order to Customer Request) calculations, the Dringu middleman got a score of 91.14%, the Tegalsiwalan middleman got a score of 86.89%, the Bali distributor's assessment of the Azka Home Industry was 89.41% and the Malang distributor's assessment of the Azka Home Industry was 91.11%